CCD photometric study of the overcontact eclipsing binary system V1363 Ori - Gazeas, Kosmas; Niarchos, Panagiotis (Aerospace Research in Bulgaria, 2005)
New BVRI light curves of the eclipsing binary system V1363 Ori, based on CCD observations made at the University of Athens Observatory, are analyzed using the Wilson-Devinney light curve synthesis code and new geometric and photometric elements are derived. These elements are used together with the available spectroscopic data to compute the absolute elements of the system. The evolutionary status of the system is also discussed.
Keywords: CCD photometry; Eclipsing binaries